A standardized approach for the thoracic dissection in robotic-assisted minimally invasive esophagectomy (RAMIE). (26th November 2020) - Kingma, B F; Read, M; van Hillegersberg, R; Chao, Y K; Ruurda, J P
ABSTRACT: Robot-assisted minimally invasive esophagectomy (RAMIE) is increasingly being adopted as the preferred surgical treatment for esophageal cancer, as it is superior to open esophagectomy and a good alternative to conventional minimally invasive esophagectomy. This paper addresses the technical details of the thoracoscopic phase of RAMIE, including the operating room set-up, patient positioning, port placement, and surgical steps.